2015
DOI: 10.1111/jocn.12824
|View full text |Cite
|
Sign up to set email alerts
|

Aspirating during the intramuscular injection procedure: a systematic literature review

Abstract: Educators need to ensure that their knowledge is up to date so that what they teach is based on evidence. This may be facilitated via regular educational updates. Further research and subsequent guidance are needed to support evidence-based practice in intramuscular injection techniques in all nursing settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 24 publications
(72 reference statements)
1
19
0
14
Order By: Relevance
“…In the paediatric vaccination setting, the practice of aspirating during the administration of an intramuscular injection is unnecessary and there is no clinical reason to suggest that these principles may not be applied when using the deltoid, ventrogluteal and vastus lateralis sites in other settings. [51] There were no immediate adverse events observed in any infant. Strengths of the present study are that 1.…”
Section: Comparison Of Cry Time With Other Studymentioning
confidence: 81%
“…In the paediatric vaccination setting, the practice of aspirating during the administration of an intramuscular injection is unnecessary and there is no clinical reason to suggest that these principles may not be applied when using the deltoid, ventrogluteal and vastus lateralis sites in other settings. [51] There were no immediate adverse events observed in any infant. Strengths of the present study are that 1.…”
Section: Comparison Of Cry Time With Other Studymentioning
confidence: 81%
“…However, there is no evidence for the necessity of aspiration. It has been reported that aspiration is not necessary in injections to vastus lateralis and deltoid muscles, but can be performed in injections to the dorsagluteal region due to its proximity to the gluteal artery (Hogan, ; Ipp et al., ; National Health and Medical Research Council, ; Sepah, Samad, Altaf, Rajagopalan, & Khan, ; Sisson, ). Because vaccines are usually injected to body parts deprived of large blood vessels, aspiration is considered unnecessary (Taddio et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Aynı zamanda, çocukluk dönemi aşılarında ağrıyı azaltmak için aspirasyonun yapılmasına gerek olmadığı da belirtilmiştir. 21 Sadece erişkinlerde kullanılan bir bölge olan dorsogluteal bölgeye gluteal arter yakınlığından dolayı aspirasyonun gerekli olduğu, fakat diğer bölgeler için aspirasyonun gerekli olmadığı belirtilmektedir. 2,19,[22][23][24][25] Bağışıklama Danışma Komitesi "aspirasyon sonrasında enjektöre kan gelmemesinin enjeksiyonun doğru şekilde yapıldığının bir göstergesi olmadığını", üstelik çocuklarda önerilen enjeksiyon bölgesinde büyük kan damarlarının olmaması nedeni ile de ağ-rıya neden olabilen bir uygulama olduğunu ifade etmektedir.…”
Section: Aspi̇rasyon Yapmaunclassified
“…2,19,[22][23][24][25] Bağışıklama Danışma Komitesi "aspirasyon sonrasında enjektöre kan gelmemesinin enjeksiyonun doğru şekilde yapıldığının bir göstergesi olmadığını", üstelik çocuklarda önerilen enjeksiyon bölgesinde büyük kan damarlarının olmaması nedeni ile de ağ-rıya neden olabilen bir uygulama olduğunu ifade etmektedir. 7,[21][22][23] Ipp. ve ark., hemşirelerin %97'sinin kan kontrolünü olması gerekenden çok daha kısa sü-rede (5-10 saniyeden kısa) yaptığını ve bu süre içinde enjektör içine kan geldiğini görmenin çok zor olduğunu belirtmişlerdir.…”
Section: Aspi̇rasyon Yapmaunclassified